Evaluation of Green Procurement Practices Among Mining Companies' Hospitals in Ghana: A Qualitative Analysis - Du Jian Guo; Patrick Boateng Sarpong; Henry Asante Antwi; Isaac Adjei Mensah (SAGE Publishing, 2020)
This study focuses on the evaluation of the green procurement practices among 7 mining hospitals in Ghana via qualitative analysis techniques. Thus, in this study, based on a 5-year case study, the practices of procurement officers in 7 hospitals belonging to mining companies in Ghana are explored. Within this period, interviews were conducted with key persons with recognizable responsibilities within the supply chain and procurement setup of the facilities. Details of their procurement practices, procedures, and policies were analyzed. A qualitative approach to organizational learning and practice is used to appreciate the existence of these differences observed and also to give a meaning to new perspectives on the challenges in establishing green procurement in the 7 mining companies' hospitals. The results of the analysis demonstrated that adjustments in the buyers' practices are not as much dependent on whether they understand, for instance, policies, tools, and procedures, but rather a matter of whether the buyers actually put their knowledge into practice.